Analisis Proses Morfologi dalam Pupulan Puisi Padang Tuh Karya Tudekamatra (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aimed to describe the morphological processes consisting of affixation, reduplication, and compounding found in Pupulan Puisi Padang Tuh written by Tudékamatra. The study employed a descriptive qualitative method with a morphological approach. The data source was Pupulan Puisi Padang Tuh, which consists of 86 poems. The data were words containing affixation, reduplication, and compounding processes. Data were collected through documentation, reading, and note-taking techniques. The data were analyzed using qualitative descriptive techniques involving identification, classification, interpretation, and conclusion drawing. The results showed that affixation, reduplication, and compounding were found in the poetry collection. Affixation was the most dominant morphological process compared to reduplication and compounding. The use of these morphological processes reflects the richness of Balinese vocabulary and the poet’s ability to utilize linguistic elements in creating aesthetic and meaningful literary expressions. Therefore, morphological processes in poetry function not only as word-formation devices but also as aesthetic tools to strengthen the message conveyed in literary works.